Satiety testing in diabetic gastroparesis: Effects of insulin pump therapy with continuous glucose monitoring on upper gastrointestinal symptoms and gastric myoelectrical activity - Koch, Kenneth L.; Hasler, William L.; Van Natta, Mark; Calles‐Escandon, Jorge; Grover, Madhusudan; Pasricha, Pankaj J.; Snape, William J.; Parkman, Henry P.; Abell, Thomas L.; McCallum, Richard W.; Nguyen, Linda A.; Sarosiek, Irene; et al. (Neurogastroenterology and motility, 2020)
Background Symptoms induced by caloric or non‐caloric satiety test meals and gastric myoelectrical activity (GMA) have not been studied in patients with diabetic gastroparesis (DGP) before and after intense glucose management. Aims We determined the effects of continuous subcutaneous insulin infusion (CSII) with continuous glucose monitoring (CGM) on GI symptoms, volume consumed, and GMA induced by the caloric meal satiety test (CMST) and water load satiety test (WLST) in DGP. Methods Forty‐five patients with DGP underwent CMST and WLST at baseline and 24 weeks after CSII with CGM. Subjects ingested the test meals until they were completely full. Visual analog scales were used to quantify pre‐ and postmeal symptoms, and GMA was recorded with cutaneous electrodes and analyzed visually and by computer. Key Results At baseline and 24‐week visits, nausea, bloating, abdominal discomfort, and fullness were immediately increased after CMST and WLST (Ps < 0.01). The meal volumes ingested were significantly less than normal controls at both visits in almost one‐third of the subjects. After the CMST, the percentage 3 cycle per minute GMA increased and bradygastria decreased compared with WLST (Ps < 0.05). After treatment for 24 weeks meal volumes ingested, postmeal symptoms and GMA were no different than baseline. Conclusions and inferences (a) Satiety test meals elicited symptoms of nausea, bloating, and abdominal discomfort; (b) CMST stimulated more symptoms and changes in GMA than WLST; and (c) CSII with CGM for 24 weeks did not improve symptoms, volumes ingested, or GMA elicited by the two satiety test meals in these patients with diabetic GP. Satiety tests in diabetic gastropresis are useful to study acute postprandial symptoms and GMA, but these measures were not improved by intensive insulin therapy. Water load and caloric load satiety tests immediately increase symptoms associated with gastroparesis. Normal 3 cpm gastric myoelctrical activity increased more after caloric load than water load tests. After 24 weeks of insulin therapy there were no differences in volumes ingested, symptoms or gastric myooelectrical activity.